Kecemasan Menghadapi Pertandingan pada Atlet Bola Basket - Arifin, Fakhrul (VISA: Journal of Vision and Ideas, 2024)
Anxiety becomes a very clear situation as the competition approaches, and it's certainly a reason for the athletes' poor performance on the court. This happened to basketball players. This research aims to describe how anxiety affects 120 basketball players who have previously participated in competitions. The method used in this research is a descriptive method that provides a clear picture of a situation as possible without any special treatment of the object being studied. The scale used is the Sport Anxiety Scale (SAS). The item discrimination test consists of 21 items with total scores ranging from 0.556 to 0.881, and it can be said to be of good quality with a reliability of 0.963. This research obtained a hypothetical mean value of 63 and an empirical mean value of 77.19, which falls into the moderate sport anxiety scale. It can be concluded that this can cause disturbances to the concentration and physiological changes of basketball players when facing a competition.